The impact of packaging environmental cues on purchase intention and brand image - França, Inês Pinto (My University, 2024)
People's shopping habits have progressively transformed to reflect their desire to make some kind of positive impact on environmental protection. However, before consumers can take advantage of sustainable innovations, they need to be able to define sustainable packaging, tell it apart from conventional packaging, and weigh the advantages when making decisions. Therefore, it is important to look at how consumers recognize packaging as environmentally friendly in addition to identifying the cues that consumers use to do so. Analyzing the potential effects of packaging environmental cues on consumers' purchase intentions and brand image are the main goals of this study. The quantitative methodology is used in this study, more precisely the experimental method. Online surveys were employed as a means of gathering data. There were two experimental conditions for the independent variable: conventional packaging vs sustainable packaging, each one with two different product categories. Additionally, the independent and dependent variables were mediated by the perception of the packaging. According to the results, packaging environmental cues conduct to a more positive brand image and more purchase intentions than conventional packaging, and these relationships are mediated by the perception of sustainable packaging. The limitations of this research are discussed, as well as suggestions for future research.
Keywords: Environmental cues; Sustainability; Packaging; Brand image; Purchase intention